Penguatan Daya Saing Usaha Mikro Kecil Menengah Melalui E-Commerce - Andriyanto, Irsad (Universitas Islam Negeri Sunan Kudus, 2018)
MSMEs have faced many challenges, especially in marketing its products, consequently the use of information technology is a necessity in the midst of rapid business changes. This study aimed to analyze the use of e-commerce in strengthening MSMEs competitiveness in terms of operations and marketing. The research took place in Kudus, a city that is pro-investment, where there are many MSMEs with various business fields. The respondents were the owners of the embroidery business in Padurenan village that was the center of the embroidery and convection industry in Kudus. They were asked about the use of e-commerce in supporting their business in terms of operation and marketing activities. Data then analyzed through qualitative technique analysis in order to conclude the research problem. As the results of the study, it’s concluded that the use of e-commerce impacted on broader marketing area, cost reduction, more relation, ease of transaction, and additional income. Besides there were some concequencies such as higher competition, plagiarism, and prone to fraud recognized as threats of the e-commerce implementation.Keywords: empowerment, competitiveness, e-commerce, threats, marketing.